Seeing the forest and the trees: Disentangling autism phenotypes in the age of DSM-5 - Volkmar, Fred R.; Woodbury-Smith, Marc; Øien, Roald A. (Development and Psychopathology, 2021)
This paper, written in honor of Professor Ed Zigler, focuses on some of the themes in developmental disabilities research that were so central to his work. It has now been nearly 80 years since Leo Kanner first identified the prototypic form – early infantile autism – of what is now autism spectrum disorder. In this article we summarize the development of the concept and the important accumulation of knowledge over time that has now led us to the recognition of a broader autism phenotype just as, at the same time, the current official diagnostic system in the USA has narrowed the concept. We also address current controversies regarding autism as the diagnosis is impacted by age and developmental factors, gender, and cultural issues. In parallel to the work on intellectual deficiency and development pioneered by Zigler and his colleagues, we summarize some of the challenges for the years ahead.
8 citations (Crossref) [2023-10-31] Type: Article tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85102496361
Keywords: Autism Spectrum Disorder; Autistic Disorder; Diagnostic and Statistical Manual of Mental Disorders; Humans; Phenotype; Psychology; Recognition; autism; dept.sed; human; peer-reviewed; phenotype